Synthesis, Characterization, and Thermal Behavior of Nanoparticles of Mg(OH)2 to Be Used as Flame Retardants - A. A. Hanna; A. S. Abdelmoaty; M. A. Sherief (Journal of Chemistry)
To study the effects of the precursor materials on the structure, the morphology, and the thermal stability of Mg(OH)2 particles, five samples were prepared by using the same method. The produced powder was characterized by using FTIR, XRD, SEM, and TEM, and the thermal stability was studied by using the thermogravimetric analysis. This study aims to use the advantage prepared material as a flame-retardant for the polymeric materials. The characterization of the obtained samples shows that Mg(OH)2 is formed in hexagonal phase and arranged in different shapes. The analysis of the data obtained from the TGA shows that Mg(OH)2 in general decomposed in three steps, the first one due to the water content and the other volatile materials, the second step represents the decomposition of Mg(OH)2 to produce MgO, and the third step represents the conversion of MgO to glassy layer. The samples prepared in presence of the surfactants gave a higher value for the formation of the glassy layer so that it is recommended to use this sample as flame retardant for the polymeric materials.